2021
DOI: 10.3390/vaccines9030292
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Willingness among Chinese Adults under the Free Vaccination Policy

Abstract: (1) Background: China will provide free coronavirus disease 2019 (COVID-19) vaccinations for the entire population. This study analyzed the COVID-19 vaccination willingness rate (VWR) and its determinants under China’s free vaccination policy compared to a paid vaccine. (2) Methods: Data on 2377 respondents were collected through a nationwide questionnaire survey. Multivariate ordered logistic regression models were specified to explore the correlation between the VWR and its determinants. (3) Results: China’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 28 publications
5
60
4
1
Order By: Relevance
“…Lastly, respondents who had a positive attitude towards the COVID-19 vaccines had a significantly higher acceptance rate of the COVID-19 vaccine which was supported by the findings in South Africa, 47 Ethiopia, 48 and the USA. 60 The current finding clearly showed that continuous awareness promotion on the necessity of the COVID-19 vaccine should be undertaken utilizing various information dissemination methods.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Lastly, respondents who had a positive attitude towards the COVID-19 vaccines had a significantly higher acceptance rate of the COVID-19 vaccine which was supported by the findings in South Africa, 47 Ethiopia, 48 and the USA. 60 The current finding clearly showed that continuous awareness promotion on the necessity of the COVID-19 vaccine should be undertaken utilizing various information dissemination methods.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, participants who had health insurance showed a significantly higher acceptance rate of COVID-19 vaccines which was in line with the findings in the USA 52 and China. 60 There was a wide range of acceptance rates among participants; those who live in High-Income countries had the highest acceptance rate (70.2%), whereas those who live in LMIC had the lowest acceptance rate (57.4%). 20 But, according to the report of the Ethiopian ministry of health, the COVID-19 vaccine is given for free for Ethiopians.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, a previous meta-analysis showed that the majority of HCWs could accept a mandatory vaccination policy, suggesting that it could be accepted if necessary 35 . Furthermore, free vaccination policy may also contribute to increase vaccination rates and the result has been validated by a study conducted in China 36 .…”
Section: Discussionmentioning
confidence: 88%
“…All investigators recruited in the 27 cities received standardized training before the interviews. Before the roll-out of the nationwide vaccination program in China, face-to-face interviews were conducted from 30 May to 10 June 2020 on respondents who intended to COVID-19 vaccinate and the unvaccinated [ 33 ]. All participants were informed about the purpose of the survey and gave informed consent.…”
Section: Methodsmentioning
confidence: 99%